The structure of coal market in China : pricing mechanism and market efficiency - Goh, Emilyn Shi Min (2014)
Since the reform and opening up in 1978, the coal industry in China has been developing rapidly. This study explores the market competitiveness and the pricing regime of the coal market structure in China by adopting quantitative research methods, namely the Herfindahl-Hirschman Index (HHI) and the Marginal Cost-Pricing. The HHI provides a broad perspective on the level of the market concentration and competitiveness while the Marginal Cost-Pricing delves deeper to examine on the market structure and the pricing decisions make for domestic coal price of the coal industry in China. HHI findings present that there is the low market concentration of the coal industry and a highly competitive coal market from 2005 to 2012.The Marginal Cost Pricing demonstrates that it has yet to achieve a perfectly competitive market structure from year 2008 to 2012. The findings have also suggested that the pricing mechanism does not set itself according to the marginal or average cost; coal pricing decisions in China have seemed to be influenced by other additional factors such as the depletable nature of coal resources and the macroeconomic variants such as global coal and oil prices.